Analysis of Student Tolerance Character Values in Grade VI SD Inpres 3 Tondo - Rahmawati, Sri; Herlina, Herlina; Nuraini, Nuraini; Zulnuraini, Zulnuraini; Muslim, Muslim (Journal of Educational Sciences, 2025)
This study aims to determine the value of student tolerance character in grade IV of SD Inpres 3 Tondo. This study uses a qualitative method with a qualitative descriptive approach. The research sample, namely classroom teachers and grade IV students, totaled 34 students. Data collection techniques are in the form of observation, interviews, questionnaires and documentation. The research instruments used by the researcher were observation sheets, interviews and questionnaires. Based on the results of observations made by researchers in directly observing student activities participating in classroom learning. The researcher observed several aspects of tolerance that have been applied by students, namely the attitude of caring for fellow friends, respecting differences of opinion/religious differences, not bullying, helping friends of different religions and behaving well. Based on the results of interviews conducted by researchers with grade IV teachers, the results were obtained that students in grade IV had applied tolerance well. Based on the results of the questionnaire analysis that has been carried out by the researcher that the value of student tolerance character in grade IV of SD Inpres 3 Tondo is high, this is seen from the data obtained by the researcher on average 78.08%. This is good enough for students to learn to apply the values of tolerance character in students in their daily lives.